(untitled) - Bradley, Julia Case (Chicago, Ill., 1996)
This guide aims to explain the features and benefits unique to Visual Basic. Feedback boxes allow students to test their comprehension of concepts by applying them to problems. Programming hints provide short-cuts and rules-of-thumb for improved productivity
Keywords: Basic (Computer program language),Basic (Ngôn ngữ lập trình máy tính)